Railway Tunnels Management System in South Africa – Concrete Structural Elements - Thako, Luba Jean-Pierre (Department of Civil Engineering, 2020)
A reliable transportation network is key to economic development and social well-being of communities. Since 19th century, rail transport has provided the most efficient link between South African’s wealthy mineral heartland and the seaports. In developing this rail network, a considerable number of railway tunnels were built due to the topography of the coastal regions. These tunnels are ageing, their operational and environmental conditions are constantly changing. Thus, their management practice should be optimised to adequately respond to the needs of the organisations managing them and for them to continue providing a safe and sustainable service. Therefore, this study reviewed the current railway tunnels management practice in South Africa and proposed an approach to improve it, considering the existing structures management systems. Further, it focuses on the concrete structural elements and their related defects due to the harsh environments of these tunnels. Therefore, the Procedures to enhance tunnels management applied consisted in outlining the gaps uncovered in the current railway tunnels management practice in South Africa and enhance this practice considering the structures management systems reviewed. This is done by improving the components of each module and integrating them in the proposed railway tunnels management system in South Africa. First, it dealt with the inventory module, designed inventory forms for items and for concrete structural elements and their components to record, inspect and monitor. Second, it designed a Tunnel Inspection Programme that set the inspection intervals, the requirements for the inspection team members, the tools and techniques and procedures to apply. This programme specified also the method of evaluating the defects and the definition of the score and the relative score of the components of elements and the health of the tunnel. Third, it developed a Tunnel Monitoring System that targeted the most critical and vulnerable elements and set the techniques and tools to monitor them. Finally, it integrated all the modules in the system designed. As results, this research has proposed a computerised tunnel management system that enhances the current practice in South Africa. This arises from the scrutinised practice in light of the existing structures management systems reviewed. From the analysis of the existing inventory data on railway tunnels and on the heavy haul lines in South Africa, relevant information was obtained. Thus, an inventory module has been developed comprising tunnel inventory forms that classify the items to be recorded and inspected. This module also described the concrete structural elements and their specific components. A Tunnel Inspection Programme has been designed, specifying the frequency of inspections based on the condition of tunnels, their ages, and the unpredictability and the harshness of their environments. This programme has also promoted the relevant techniques to be applied to inspect concrete structural elements and the appropriate tools to be used. Additionally, the requirements for inspection team concerning the qualifications and experience of each member have been provided. This programme has also recommended the use of the current DER rating system, emphasising that the scope of this study refers to concrete structural elements that should all be rated and recorded. Additionally, it has designed a Tunnel Monitoring System specific to the most critical and vulnerable concrete structural elements of railway tunnels. This system includes a set of tunnel monitoring strategies, the setting up of the system and the sensory system. It finally integrated all these sub-systems into the main Railway Tunnel Management System in South Africa. In conclusion, this research proposes the integrated computerised railway tunnel management system for South Africa. It also set the “big picture” of the overall tunnel structures and the tunnels on the heavy haul lines currently managed by Transnet TFR in South Africa. Additionally, it sustains the current DER rating system and proposes its application to all the defects on the concrete structural elements, instead of the worst defect on the inspected element. As recommendations, the railway tunnels authority should adopt a monitoring system for each tunnel on the heavy haul lines. Also, the authority should make available information on all existing monitoring systems on railway tunnels and the most critical data collected. Moreover, the authority should make available the previous railway tunnels inspection files to be uploaded to the proposed system. Apart from this, we recommend a further comprehensive study to integrate the inspection of non-structural elements to the proposed system. Finally, we recommend to the management authority to organise a comprehensive study of the water leakage issues on railway tunnels to better understand and adequately respond to them.